2017
DOI: 10.21307/sjcapp-2017-003
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Participating in Noncompetitive or Competitive Sports and Mental Health among Adolescents – a Norwegian Population-based Cross-sectional Study

Abstract: Background: Mental health problems in adolescents have become a major public health challenge in many western countries. Many adolescents participate in noncompetitive or competitive sports for leisure. The aim of this study was to examine the association between participation in noncompetitive or competitive sports and mental health problems among Norwegian adolescents. Method: Data from a cross-sectional survey conducted among Norwegian junior high (N=9414) and high school students (N=10,571) aged 13 to 22 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…A recent study on the effects of participating in competition in adolescence [ 50 ] found the same positive effect on mental health as our study of children. Despite the fact that children do not always win such competitive sports matches, they do offer the opportunity to experience success and might therefore improve self-esteem [ 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…A recent study on the effects of participating in competition in adolescence [ 50 ] found the same positive effect on mental health as our study of children. Despite the fact that children do not always win such competitive sports matches, they do offer the opportunity to experience success and might therefore improve self-esteem [ 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although some studies have shown statistical associations between PA and various mental health outcomes (see e.g. Breistøl et al, 2017; Doré et al, 2018; McDowell et al, 2016), many have considerable methodological weaknesses. In addition, these studies are limited in the extent to which they can explain any associations in terms of causal mechanisms, which requires a much more careful and detailed process of inference.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement in different organized activities has been associated with increased academic achievements, social relationships, life satisfaction and better mental health (Badura, Madarasova Geckova, Sigmundova, van Dijk, & Reijneveld, 2015; Breistøl, Clench‐Aas, Van Roy, & Kjærsti Raanaas, 2017; Eime, Young, Harvey, Charity, & Payne, 2013). Playgrounds and sports fields in the neighbourhood have been pointed out as the strongest predictor for active participation with friends and peers (Nordbø, Raanaas, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%